KARAKTERISTIK ORGANOLEPTIK DAN FISIKOKIMIA ONDE-ONDE DENGAN SUBSTITUSI MODIFIED CASSAVA FLOUR (MOCAF) DAN TEPUNG TALAS BENENG - Widyanto, Kadimas Wahyu; Azzahro, Fitri Oktavia; Khairunnisa, Athiya; Tyannisa, Fatiha; Nurfadillah, Safitri; Tampenawas, Russel Yehezkiel; Nurtiana, Winda (Leuit : Journal of Local Food Security, 2025)
This study aims to evaluate the organoleptic and physicochemical characteristics of onde-onde substituted with Modified Cassava Flour (MOCAF) and beneng taro flour. The product was developed in four formulations with varying proportions of glutinous rice flour, MOCAF, and beneng taro. Analyses included organoleptic tests (taste, color, aroma, texture, aftertaste), chemical parameters (moisture, ash, protein, fat, starch, carbohydrate, oxalate), color analysis using a chromameter, and microbiological safety through Total Plate Count (TPC). The best formulation was F2, consisting of 150g glutinous rice flour, 100g MOCAF, and 30g beneng taro flour. F2 showed the best results in taste, aroma, texture, and aftertaste, while F3 had the best color. Nutritional analysis showed 17.34% moisture, 1.55% ash, 3.94% protein, 11.84% fat, 30.11% starch, 65.33% carbohydrates, and 260 mg/kg oxalate. The TPC value was 30,000 CFU/gram, which is within the safe limit. This study concludes that substituting MOCAF and beneng taro flour can improve the sensory quality and nutritional value of onde-onde while maintaining its safety for consumption